PERAN MOTIVASI BELAJAR DALAM MEMEDIASI PENGARUH KEBIASAAN BELAJAR, FASILITAS SEKOLAH, DAN EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR: A Study on Vocational High School Students in the Software and Game Development Program - Septian Nur Fajar Pratama; Fakhruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the phenomenon of learning achievement being influenced by various factors, yet the role of motivation as a mediator has not been widely explored, particularly among vocational high school (SMK) students in the Software and Game Development (PPLG) major. The research aims to analyze the influence of study habits, school facilities, and parental economic status on learning achievement, with learning motivation as a mediating variable. A quantitative method with a path analysis approach was applied to 166 twelfth-grade students from the PPLG major at public SMKs in Purbalingga Regency, selected through proportionate stratified random sampling. Data were collected via questionnaires and documentation of report card grades, then analyzed using classical assumption tests, path analysis, and the Sobel test. The results reveal that learning motivation has the strongest direct positive influence on learning achievement. Study habits were proven to significantly increase learning motivation but had no direct effect on achievement, indicating that motivation acts as a full mediator in this relationship. A surprising finding was that school facilities had a significant negative effect on learning motivation and also no direct effect on achievement. Meanwhile, parental economic status had a significant direct negative influence on learning achievement, without involving the mediation of motivation. The study concludes that learning motivation is a key mechanism; therefore, efforts to improve achievement must focus on strengthening students' intrinsic motivation as the main driver of academic accomplishment.